Emerging evidence-based innovative approaches to control catheter-associated urinary tract infection: a review - Rajaramon, Shobana; Shanmugam, Karthi; Dandela, Rambabu; Solomon, Adline Princy (Frontiers in Cellular and Infection Microbiology, 2023)
Healthcare settings have dramatically advanced the latest medical devices, such as urinary catheters (UC) for infection, prevention, and control (IPC). The continuous or intermittent flow of a warm and conducive (urine) medium in the medical device, the urinary catheter, promotes the formation of biofilms and encrustations, thereby leading to the incidence of CAUTI. Additionally, the absence of an innate immune host response in and around the lumen of the catheter reduces microbial phagocytosis and drug action. Hence, the review comprehensively overviews the challenges posed by CAUTI and associated risks in patients' morbidity and mortality. Also, detailed, up-to-date information on the various strategies that blended/tailored the surface properties of UC to have anti-fouling, biocidal, and anti-adhesive properties to provide an outlook on how they can be better managed with futuristic solutions. adhere to the catheters; however, the risk is minimal because they are placed in the body for a short period (Singha et al. 2017).The European and Asian guidelines on the management of catheter-related infections list the bacterial pathogens commonly seen in short-term catheterization (Escherichia